Predicting Training Gain for a 3 Week Period of Arm Ability Training in the Subacute Stage After Stroke - Lotze, Martin; Roschka, Sybille; Domin, Martin; Platz, Thomas (Frontiers in Neurology, 2018)
Background: Biomarkers for gains of evidence based interventions for upper limb motor training in the subacute stage following stroke have rarely been described. Information about these parameters might help to identify patients who benefit from specific interventions and to determine individually expected behavioral gains for a certain period of therapy. Objective: To evaluate predictors for hand motor outcome after arm ability training in the subacute stage after stroke selected from known potentially relevant parameters (initial motor strength, structural integrity of the pyramidal tract and functional motor cortex integrity). Methods: We applied the arm ability training (AAT) over 3 weeks to a subpopulation of stroke patients with mild arm paresis, i.e. in 14 patients on average 4 weeks after stroke. The following biomarkers were measured before therapy onset: grip strength on the affected hand, transcranial magnetic stimulation recruitment curve steepness over the primary motor hand area (slope ratio between the ipsilesional hemisphere (IH) and contralesional hemisphere (CH)), and diffusion weighted MRI fractional anisotropy (FA) in the posterior limb of the internal capsule (PLIC; determined as a lateralization index between IH and CH). Outcome was assessed as the AATgain (percentage improvement over training). The “Test d'Evaluation des Membres Supérieurs de Personnes Âgées” (TEMPA) was assessed before and after training to test for possible associations of AAT with activity of daily living. Results: A stepwise linear regression identified the lateralization index of PLIC FA as the only significant predictor for AAT-gain (R2=0.519; P=0.029). AAT-gain was positively associated (r=0.59; P=0.028) with improvement in arm function during daily activities (TEMPA). Conclusions: While all mildly affected patients achieved a clinically relevant therapeutic effect, pyramidal tract integrity nevertheless had a modifying role for clinical benefit.